2022
DOI: 10.14639/0392-100x-n1952
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 airway stenosis treated by tracheal resection and anastomosis: a bicentric experience

Abstract: SUMMARY Objective The COVID-19 pandemic was an extraordinary challenge for the global healthcare system not only for the number of patients affected by pulmonary disease, but also for the incidence of long-term sequalae. In this regard, laryngo-tracheal stenosis (LTS) represents one of the most common complications of invasive ventilation. Methods A case series of patients who underwent tracheal resection and anastomosis (TRA) for post-COVID-19 LTS was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Additionally, the rate of infection transmission to healthcare workers during tracheostomy is extremely low when appropriate personal protective equipment is used (19). It has also been reported that tracheostomy at appropriate timing should be considered to avoid laryngotracheal stenosis (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the rate of infection transmission to healthcare workers during tracheostomy is extremely low when appropriate personal protective equipment is used (19). It has also been reported that tracheostomy at appropriate timing should be considered to avoid laryngotracheal stenosis (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…The most common reason for tracheal stenosis observed was prolonged mechanical ventilation and tracheostomy (PITS) [ 24 ]. The patients who had PITS had various etiologies, such as head injury, urosepsis, organic phosphorous poisoning, post-tracheostomy following extensive facial-maxillary surgery, and post-COVID-19 recovery [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among all the patients who underwent tracheal reconstruction surgeries at our tertiary care center, the major cause of tracheal stenosis was post-intubation tracheal stenosis (PITS) [ 7 , 8 ]. PITS patients were referred from different hospitals with various etiological factors during the pre-coronavirus disease 2019 (COVID-19) and post-COVID-19 periods.…”
Section: Introductionmentioning
confidence: 99%
“…The typical presentation consists of dyspnea, wheezing and stridor on physical examination occurring after several days from extubating (8,9,14). Symptoms may include dysphonia and communication difficulties (22), hoarseness, dry cough, and swallowing problems (12).…”
Section: Manifestationsmentioning
confidence: 99%
“…The raw incidence of TS seems to be higher in COVID-19 patients than in pre-COVID-19 era ( 11 ), and the medical community has been alerted to the possibility of an unprecedented surge in TS ( 12 ), despite the limited number of cases in literature does not allow to draw definitive conclusions in this regard. The mean age ranges from 50 ( 13 15 ) to 60 ( 8 , 11 , 16 ) years old, and males seem to be more prone to develop this disease, with approximately prevalence of 60%–70% ( 8 , 11 , 13 , 14 , 16 , 17 ).…”
Section: Epidemiologymentioning
confidence: 99%